An Outbreak of a New Coronavirus Infection COVID-19 in an Educational Institution in Moscow - L N Mazankova; E R Samitova; I M Osmanov; N A Dracheva; V G Akimkin (Эпидемиология и вакцинопрофилактика)
Relevance. The COVID-19 pandemic is still making adjustments to the modern realities of both healthcare and society as a whole. The incidence of COVID-19 in children and adolescents is becoming more and more urgent. At the end of January 2022, in Moscow, the number of registered cases of SARS-CoV-2 infection in minors increased 14 times (from 2,000 to 28,000), and the number of hospitalizations increased 10 times, to 120 people per day. During the pandemic, local outbreaks of COVID-19 remain relevant, especially in organized groups. Aim. Description of a local outbreak of COVID-19 in an organized educational group of common residence, preventive measures and characteristics of the infection. Materials and methods. The results of the examination of the focus of COVID-19, medical records of hospitalized patients, regulatory documents, and literary sources were used. A descriptive epidemiological method was used. Statistical data processing was not carried out due to the small sample size. Results. In the spring of 2021, an outbreak of COVID-19 was registered in one specialized educational and methodological center in Moscow with ten victims. The center is located in a five-story brick building designed for the teaching and living of pupils. When registering the first case of COVID-19 in a specialized educational and methodological center, an operating mode was established on the principle of an observatory. Nine children were hospitalized and one teenager was treated for scrap in Moscow. All hospitalized patients underwent computed tomography of the chest organs, no changes in the lungs were noted, which is a significant difference compared to adults, in whom in most cases the SARS-Cov-2 virus enters the lungs. All patients in the hospital received antiviral therapy (Umifenovir 200 mg orally 4 times a day, 5 days), decongestants, local antiseptics, antihistamines were used according to indications. At discharge, all adolescents had positive results for COVID-19 according to the results of PCR swabs from the nasopharynx and oropharynx, and therefore, with an improvement in their general condition, they were transferred for further observation to the observational rehabilitation center COVID-19 «Krylatskiye kholmy». Conclusions. Living in communal dormitories and learning at the place of residence involves close contacts at home and during classes, which predetermines a high risk of infection with the SARS-Cov-2 virus and the occurrence of foci. Promptly carried out anti-epidemic measures make it possible to interrupt the chain of infections in the outbreak. Compared to adults, adolescents experienced fewer and less severe symptoms of COVID-19. Although in most cases, children do not get severely ill from COVID-19 as adults, they can play an important role in the transmission of the infection and in the formation of its outbreak.